2023
DOI: 10.1002/lci2.71
|View full text |Cite
|
Sign up to set email alerts
|

Impact of metformin on clinical outcomes in advanced hepatocellular carcinoma treated with immune checkpoint inhibitors

Abstract: Background and Aims Non‐alcoholic steatohepatitis (NASH) is a common cause of hepatocellular carcinoma (HCC) worldwide. Emerging data suggests NASH‐induced HCC could be associated with less response to immune checkpoint inhibitor (ICI)‐based therapy. Metformin has been associated with improved outcomes in cancers like melanoma treated with ICIs, but its impact on HCC is not well defined. The purpose of this study was to examine the effect of metformin on clinical outcomes in patients with advanced HCC treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…Conversely, the utilization of metformin was found to have no prognostic impact in a cohort of patients with advanced HCC who received Lenvatinib as a rst-line treatment. Recently, Kang and colleagues performed an analysis on a cohort of patients treated with immunotherapy for advanced HCC and highlighted worse survival outcomes in patients included in the metformin group compared to those in the no-metformin groups, even without reaching the statistical signi cance (11). Our study encompassed a larger patient sample receiving rst-line treatment for advanced HCC (Atezolizumab plus Bevacizumab or Lenvatinib), whereas the previous study focused exclusively on patients who received immunotherapy in either the rst or subsequent lines of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the utilization of metformin was found to have no prognostic impact in a cohort of patients with advanced HCC who received Lenvatinib as a rst-line treatment. Recently, Kang and colleagues performed an analysis on a cohort of patients treated with immunotherapy for advanced HCC and highlighted worse survival outcomes in patients included in the metformin group compared to those in the no-metformin groups, even without reaching the statistical signi cance (11). Our study encompassed a larger patient sample receiving rst-line treatment for advanced HCC (Atezolizumab plus Bevacizumab or Lenvatinib), whereas the previous study focused exclusively on patients who received immunotherapy in either the rst or subsequent lines of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Discordant evidences about the metformin's antineoplastic properties have been highlighted (8-10). Recently, Kang and collaborators conducted a retrospective analysis on 111 patients affected by advanced HCC who received immune checkpoint inhibitors (ICIs) and demonstrated that the use of metformin was associated with a trend towards worse objective response rates (ORR), overall survival (OS), and progression-free survival (PFS), even without reaching statistical signi cance (11). Building upon these ndings, the aim of the present study was to investigate the potential prognostic role of metformin use and other concomitant medications (such as statins, insulin, and aspirin) in a cohort of advanced HCC patients who received Lenvatinib or Atezolizumab plus Bevacizumab as rst-line treatment.…”
Section: Introductionmentioning
confidence: 99%